Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have $f(x)=g(ax+b)$, a and b are constant.

I need to show that $\nabla f(x)=a\nabla g(x)$ and $\nabla^2 f(x)=a^2\nabla^2 g(x)$...

I was thinking that the final answer should have ax+b in it, but apparently it can be shown that the above is true???

share|improve this question
    
What is $*$? Explain your notation. –  glebovg Nov 26 '12 at 2:46
1  
I believe you should have $\nabla^2 f=a^2\nabla^2 g$ (you're missing the 'squared'). –  icurays1 Nov 26 '12 at 3:02
    
i just corrected it –  ASROMA Nov 26 '12 at 3:09
    
The formulas should be $\nabla f(x) = a \nabla g(ax + b)$ and $\nabla^2 f(x) = a^2 \nabla^2 g(ax + b)$. (I just provided a derivation below.) –  littleO Nov 26 '12 at 5:41

1 Answer 1

up vote 2 down vote accepted

In this problem $f(x) = g(h(x))$, where $h(x) = ax + b$. I'm going to consider the case where $a$ is a matrix rather than a scalar, because it's useful and no more difficult. You can assume $a$ is a scalar if you'd like.

Let's establish some notation. Recall that if $F:\mathbb R^n \to \mathbb R^m$ is differentiable at $x$, then $F'(x)$ is an $m \times n$ matrix. In the special case where $m = 1$, $F'(x)$ is a $1 \times n$ matrix. I'm going to use the convention that $\nabla F(x) = F'(x)^T$, so $\nabla F(x)$ is a column vector rather than a row vector. Then $G(x) = \nabla F(x)$ is a function from $\mathbb R^n \to \mathbb R^n$, and $\nabla^2 F(x) = G'(x)$, which is an $n \times n$ matrix.

The chain rule tells us that \begin{align} f'(x) &= g'(h(x))h'(x) \\ &= g'(ax + b) a. \end{align} It follows that \begin{align} \nabla f(x) &= a^T g'(ax+b)^T \\ &= a^T \nabla g(ax + b). \end{align} That is our formula for $\nabla f(x)$.

Preparing to use the chain rule again, we can express $\nabla f(x)$ as $\nabla f(x) = w(h(x))$, where $w(x) = a^T \nabla g(x)$. Note that $w'(x) = a^T \nabla^2 g(x)$. Applying the chain rule to $z(x) = \nabla f(x) = w(h(x))$, we see that \begin{align} \nabla^2 f(x) &= w'(h(x))h'(x) \\ &= a^T \nabla^2 g(ax + b) a. \end{align} This is our formula for $\nabla^2 f(x)$.

share|improve this answer
1  
i knew that this properties from book have an answer with a and b included. I was trying to find a way to show the following:$\nabla f(x)=a\nabla g(x)$ and $\nabla^2 f(x)=a^2\nabla^2 g(x)$ –  ASROMA Nov 26 '12 at 5:56
    
What makes you think that should be true though? It contradicts the formulas from your book. (You could easily find an example where the two different expressions for $\nabla f(x)$ aren't equal.) –  littleO Nov 26 '12 at 5:59
    
since a and b are constants, i think somehow we can show that $\nabla h(ax+b)= a \nabla h(x)$ –  ASROMA Nov 26 '12 at 6:08
2  
thanks though for the answer –  ASROMA Nov 26 '12 at 6:24

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.